Seasonal transcriptomic shifts reveal metabolic flexibility of chemosynthetic symbionts in an upwelling region - Isidora Morel-Letelier; Benedict Yuen; Luis H. Orellana; A. Carlotta Kück; Yolanda E. Camacho-García; Minor Lara; Matthieu Leray; Laetitia G. E. Wilkins (mSystems)
ABSTRACT Upwelling in the Tropical Eastern Pacific profoundly affects marine coastal ecosystems by driving drastic seasonal changes in water temperature, oxygen levels, and nutrient availability. These conditions serve as a natural experiment that provides a unique opportunity to study how marine animals and their associated microorganisms respond in the face of environmental change. Lucinid bivalves host chemosynthetic Candidatus Thiodiazotropha symbionts equipped with diverse metabolic pathways for sulfur, carbon, and nitrogen use. However, how these symbionts employ their metabolic toolkit in a changing environment remains poorly understood. To address this question, we conducted metagenomic and metatranscriptomic analyses of Ctena cf. galapagana symbionts before and during a Papagayo upwelling event in Santa Elena Bay, Costa Rica. The C. cf. galapagana were co-colonized mainly by two Ca. Thiodiazotropha symbiont clades regardless of the sampling season. We observed a concerted shift in the transcriptomic profiles of both symbiont clades before and during upwelling, suggesting changes in energy source use. Dissimilatory methanol oxidation genes were upregulated before upwelling, while sulfide oxidation genes were upregulated during upwelling. These physiological changes were potentially driven by upwelling-induced changes in sediment biogeochemistry and resource availability. Our findings highlight the adaptability of the lucinid symbiosis and the crucial role of symbiont metabolic flexibility in their resilience to environmental challenges.IMPORTANCEThe oceans are undergoing rapid change, and marine animals together with their associated microorganisms must adjust to these changes. While microbes are known to play a critical role in animal health, we are only beginning to understand how symbiotic relationships help animals cope with environmental variability. Annual upwelling events cause drastic and abrupt increases in nutrient availability and productivity, while temperature and oxygen decrease. In this study, we investigated how bacterial symbionts of the lucinid bivalve Ctena cf. galapagana respond to upwelling in the Tropical Eastern Pacific. The symbionts, from the genus Candidatus Thiodiazotropha, are chemosynthetic (i.e., they use inorganic chemicals for energy and fix carbon) and provide nutrition to their host. Our results show that these symbionts adjust their use of different energy sources in response to environmental changes that affect resource availability. This metabolic flexibility underscores the resilience of animal-microbe relationships in coping with environmental change.